ОРГАНИЗАЦИОНИ ЕФЕКТИ УЛАСКА ЗДРАВСТВЕНИХ УСТАНОВА У СИСТЕМ ЗДРАВСТВЕНОГ ТУРИЗМА (Baština, 2023)
The importance of the effect of the organization of health institutions on the system of health tourism is important not only from the point of view of scientific management theory, but, above all, in order to make strategically important decisions for the further functioning and development of the new, reformed health care system in Serbia. In the new organizational environment, healthcare workers will have a new and more complex role.The organization of health institutions and the role of employees in health care will be directed towards the users of health services with constant work on their own education, as service providers, as well as the education and information of users. Healthcare has characteristics that distinguish it from other fields. Specific characteristics include knowledge of health services and their value. Effective organization of health institutions in the health tourism system is essential for creating a high impact health system.
Keywords: здравствени туризам, здравствени систем, менаџмент, организација, ефекти